DAMPAK PERMASALAHAN HIDUP EMPAT TOKOH UTAMA TERHADAP KEPRIBADIAN DALAM NOVEL AUTO KARYA NATSUO KIRINO - Nur Hastuti (Universitas Diponegoro, 2014)
Abstract This ressearch has title” The Impact of The Fourth Main Characters’ Life Problem Toward Their Characteristic In The Novel Auto By Natsuo Kirino”. The objects ressearch is novel Auto by Natsuo Kirino that was published in 1997. This ressearch has aim to get the description of characteristic structure of the four main characters that includes id, ego, and superego, and also about what are the effects of life problem toward their characteristics. The theoritical approach that is used in this ressearch is to answer those both problems and uses Sigmund Freud’s Psychoanalisist.From the characteristics ressearch result of the four main characters, they are Masako, Yayoi, Yoshie, and Kuniko, it is proved that their characteristics are more dominated by id impuls than ego impuls or superego. This is because work characteristic of id is pleasure principle to reduce tension or problem.The impact of life problem toward the characteristic of four main characters is descibed below. Masako has problem when she is never respected in her workplace. Difficult communication with her husband and her household that is not harmonious and her relationship with her children is not getting well. Those problems effect she does main action to reduce her tension in her life. She also helps her friend, Yayoi by throwing away Yayoi’s husband corpse that had been mutilated. Yayoi has problem with her husband who never respects her and her household that is not harmonious. Solution that is done by Yayoi because of household problem is by doing main action by killing her husband. Another character, Yoshie has a problem where she must nurse her mother in law who always grumble and gets angry to her when she come late. She must also work in the night to earn money to fulfill her needs. Those facts cause fury to Yoshie, so that she wants to kill her mother in law. Yoshie wants to leave out all her burdens and tensions by helps Masako to throw away Kenji’s corpse (Yayoi’s husband). Another character, Kuniko has problem about she feel that she has no face beauty and perfect body shape, so that she lives in luxurious way and has many debts to the creditors to cover her lack. She does this way to reduce her tension in her life. Keywords: novel, main character, life problem, psychoanalisist